If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 11 + -2x = x + 2x + 16 Reorder the terms: 11 + 6x + -2x = x + 2x + 16 Combine like terms: 6x + -2x = 4x 11 + 4x = x + 2x + 16 Reorder the terms: 11 + 4x = 16 + x + 2x Combine like terms: x + 2x = 3x 11 + 4x = 16 + 3x Solving 11 + 4x = 16 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 11 + 4x + -3x = 16 + 3x + -3x Combine like terms: 4x + -3x = 1x 11 + 1x = 16 + 3x + -3x Combine like terms: 3x + -3x = 0 11 + 1x = 16 + 0 11 + 1x = 16 Add '-11' to each side of the equation. 11 + -11 + 1x = 16 + -11 Combine like terms: 11 + -11 = 0 0 + 1x = 16 + -11 1x = 16 + -11 Combine like terms: 16 + -11 = 5 1x = 5 Divide each side by '1'. x = 5 Simplifying x = 5
| 31g=g-26 | | 11x-18=-7 | | 4y+15=39 | | 6a+13=-5 | | 4x+7=-3x+21 | | 10x-7=40x+5 | | 3y+2=9x+8 | | 138-3x=33x+18 | | 9-7x=204-42x | | 5x+2+6=2x+28+x | | 3x-y+6x+7y= | | 15x+5=755 | | -5(b-7)-3b=-23 | | X+x^2=90 | | -5=2+w | | 2x+3x+4x= | | 11-9x=28-16x | | 8*(x-2)+16=7*(x+2) | | 3x+(-8)=-71 | | 3x-5x+x=10 | | 9x^2-2=0 | | 2x-4(x+2)=5x+6 | | 5x+6b=45 | | s=p+16 | | 4(3w-7)=32 | | x+1.1=8.1 | | -7u=-21 | | A+7.2=4 | | x+9.1=-6.9 | | (x-19)2=4 | | 4(5q-4)-[2(3q-3)+5]= | | x+-3=-1 |